Combustion Synthesis and Enhancement of BiOCl by Doping Eu3+ for Photodegradation of Organic Dye. Issue 3 (9th November 2015) - Gao, Meichao; Zhang, Dafeng; Pu, Xipeng; Shao, Xin; Li, Hong; Lv, Dongdong
Abstract : Eu 3+ ‐doped BiOCl with different doping concentrations was synthesized by a simple combustion method. The as‐synthesized photocatalysts were characterized by X‐ray diffraction, scanning electron microscope, transmission electron microscope, Raman spectroscopy, X‐ray photoelectron spectroscopy, electron paramagnetic resonance spectroscopy, and UV–vis diffuse reflectance spectroscopy. The experimental results show that Eu 3+ was successfully doped into the lattice of BiOCl. The as‐synthesized Eu 3+ ‐doped BiOCl photocatalysts show a more intense continuous absorption in UV light region, accompanied with decreased energy band gap. Moreover, the Eu 3+ doping leads to the formation of oxygen vacancies, small crystallite size, and high specific surface areas. Compared with pure BiOCl, the Eu 3+ ‐doped BiOCl photocatalysts exhibits much higher photocatalytic activity for Rhodamine B (RhB) under UV light irradiation. As‐obtained Eu 3+ ‐doped BiOCl can be easily reused with excellent stability. In addition, the mechanism of the improved photocatalytic properties of Eu 3+ ‐doped BiOCl was discussed in detail.